The time-effect model of nitrogen and phosphate uptake by Potamogeton crispus L in eutrophic water body. (October 2018) - Zhang, C Y; Wang, L P; Xu, D L; Wan, L; Yin, C B
Abstract: In this study, the effects of Potamogeton crispus L on total nitrogen (TN) and total phosphate (TP) in a eutrophic water body were explored and a time-effect model was developed for nitrogen and phosphate uptake by P . crispus . The results revealed that i) TN and TP in eutrophic water showed a trend of first decline and then increase at different P . crispus biomass levels; ii) at the same nutrient level, the amount of TN and TP uptake by P . crispus increased with increasing biomass; and iii) at the same biomass conditions, the amount of TN and TP uptake by P . crispus was the highest at nutrient levels of 13.95-20.56 mg/L for TN and 0.037-0.263 mg/L for TP. Moreover, a time-effect model was developed for TN and TP uptake by P . crispus in eutrophic conditions, as well as a TN and TP limit theoretical model. Using multiple sets of data, it was demonstrated that the models were well fitted with error rates of less than 10%. Overall, the study provides a strong basis for optimal P . crispus biomass input and harvest time in ecological restoration of eutrophic water bodies.